Power-sharing, conflict resolution, and the logic of pre-emptive defection. (July 2021) - Johnson, Chelsea
Conclusions about the potential for peace via power-sharing are mixed. For some, power-sharing does little to overcome the commitment problem characterizing a transition from conflict, while others argue that such concessions provide signals of parties' willingness to incur costs. This article develops and tests a new theory, aiming to shed light on the mechanisms through which power-sharing bargains help to overcome the commitment problem. I argue that government parties tend to hold an electoral and military advantage, which heightens incentives for rebel leaders to defect from a settlement prior to conceding their capacity to use violence. Where settlements provide discrete guarantees that offset the risks of electoral defeat and the co-optation of forces, these incentives for pre-emptive defection should be mitigated. I offer a novel disaggregation of provisional power-sharing subtypes, distinguishing between long-term and short-term arrangements. The analysis rests on an original, cross-national dataset of government-and-rebel dyads to negotiated settlements signed between 1975 and 2015 (N = 168). The logistic regression results clearly indicate that power-sharing settlements stipulating 'consociational'-style reforms are significantly more likely to resolve conflict between settlement dyads, all else equal. Meanwhile, standard conceptualizations of power-sharing, which include transitional coalitions and troop integration, appear unlikely to secure rebel commitment beyond the transition period, which helps to explain the contradictory findings in existing research.